2018
DOI: 10.1080/01652176.2018.1521537
|View full text |Cite
|
Sign up to set email alerts
|

TRH-induced secretion of adrenocorticotropin and cortisol in dogs with pituitary-dependent hypercortisolism

Abstract: Background: In dogs, spontaneous Cushing’s syndrome is most often pituitary-dependent and caused by hypersecretion of adrenocorticotropic hormone (ACTH), resulting in increased adrenocortical glucocorticoid secretion similar to horses. In horses with Cushing’s syndrome (or pituitary pars intermedia dysfunction [PPID]) a thyrotropin-releasing hormone (TRH) stimulation test can be used for diagnosis, as TRH administration results in increased circulating ACTH and cortisol concentrations in affected horses.Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It releases stored proopiomelanocortin, which is then converted into ACTH and other peptides by prohormone convertases ( 38 ). A previous study reported the presence of TRH receptors in the pituitary and adrenal glands of dogs ( 39 ). However, plasma cortisol concentration did increase significantly after TRH stimulation, whereas plasma ACTH concentration did not rise significantly ( 39 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It releases stored proopiomelanocortin, which is then converted into ACTH and other peptides by prohormone convertases ( 38 ). A previous study reported the presence of TRH receptors in the pituitary and adrenal glands of dogs ( 39 ). However, plasma cortisol concentration did increase significantly after TRH stimulation, whereas plasma ACTH concentration did not rise significantly ( 39 ).…”
Section: Discussionmentioning
confidence: 95%
“…A previous study reported the presence of TRH receptors in the pituitary and adrenal glands of dogs ( 39 ). However, plasma cortisol concentration did increase significantly after TRH stimulation, whereas plasma ACTH concentration did not rise significantly ( 39 ). This suggests the possibility of hypercortisolism, which can be induced by direct TRH stimulation of the adrenal gland.…”
Section: Discussionmentioning
confidence: 95%